Sharia Influencer Effect on Islamic Savings Intention among Generation Z in Indonesia - Acu Kusnandar (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
Digital transformation has reshaped the way Islamic financial literacy is delivered, particularly through social media platforms where Generation Z actively consumes information and forms financial intentions. However, limited studies have examined how Sharia influencers operating on different platforms contribute to Islamic savings intention, especially within a comparative digital context. This study aims to analyze the effectiveness of Sharia influencers on Instagram and TikTok in shaping Generation Z’s interest in Islamic savings products in Indonesia. A quantitative approach was employed using a survey of 159 Generation Z respondents who had been exposed to Sharia influencer content. Data were analyzed using Exploratory Factor Analysis (EFA), reliability testing, multiple regression analysis, and independent-samples t-tests. The findings reveal two dominant dimensions of Sharia influencer effectiveness, namely trust and relevance, as well as education and content consistency. Regression results indicate that educational value, content relevance, and Islamic value communication significantly influence interest in Islamic savings, while trust and attractiveness do not show significant direct effects. Furthermore, Instagram demonstrates stronger effectiveness than TikTok in influencing interest, suggesting deeper cognitive engagement and stronger credibility formation. These results highlight that Islamic financial intention among Generation Z is primarily driven by meaningful, educational, and value-based digital content rather than superficial influencer appeal. The study contributes to Islamic marketing and behavioral finance literature by emphasizing the role of platform-specific communication strategies in strengthening Islamic financial inclusion. ABSTRAK - Pengaruh Influencer Syariah terhadap Niat Menabung Syariah di Kalangan Generasi Z di Indonesia. Perkembangan teknologi digital telah mengubah pola penyampaian literasi keuangan syariah, khususnya melalui media sosial yang menjadi ruang utama bagi Generasi Z dalam mengakses informasi dan membentuk minat keuangan. Meskipun demikian, kajian yang membandingkan peran influencer syariah lintas platform dalam membentuk minat terhadap tabungan syariah masih relatif terbatas. Penelitian ini bertujuan untuk menganalisis efektivitas influencer syariah di Instagram dan TikTok dalam membentuk minat Generasi Z terhadap produk tabungan syariah di Indonesia. Penelitian ini menggunakan pendekatan kuantitatif melalui survei terhadap 159 responden Generasi Z yang telah terpapar konten influencer syariah. Analisis data dilakukan dengan Exploratory Factor Analysis (EFA), uji reliabilitas, regresi linier berganda, serta uji beda independent-samples t-test. Hasil penelitian mengidentifikasi dua dimensi utama efektivitas influencer syariah, yaitu dimensi kepercayaan dan relevansi, serta dimensi edukasi dan konsistensi konten. Analisis regresi menunjukkan bahwa nilai edukatif, relevansi konten, dan penyampaian nilai-nilai Islam berpengaruh signifikan terhadap minat tabungan syariah, sementara kepercayaan dan daya tarik influencer tidak menunjukkan pengaruh langsung. Temuan lainnya menunjukkan bahwa Instagram lebih efektif dibandingkan TikTok dalam membentuk minat tabungan syariah, yang mengindikasikan adanya proses pemrosesan kognitif yang lebih mendalam serta pembentukan kredibilitas yang lebih kuat pada platform tersebut. Secara keseluruhan, hasil penelitian menegaskan bahwa minat keuangan syariah Generasi Z lebih dipengaruhi oleh konten yang bersifat edukatif, relevan, dan berbasis nilai, dibandingkan aspek visual atau popularitas influencer semata. Penelitian ini berkontribusi pada literatur pemasaran Islam dan perilaku keuangan dengan menekankan pentingnya strategi komunikasi digital yang selaras dengan karakteristik platform dalam mendorong inklusi keuangan syariah.